Engineering properties of laterite aggregate as coarse aggregate replacement in concrete - Mohd Al-Adham, Ismail (2012)
The experiment is carried out in order to investigate the properties of laterite aggregate used in producing concrete mix. Laterite aggregate is chosen because it is widely spread in tropical country like Malaysia. The aggregates, which turn up to be strongest and more durable upon exposure to repetitive sun and rain might also served as a perfect replacement for' granite aggregates. The experiment was conducted in the laboratory to investigate the properties of the concrete in term of their aggregate, workability of fresh concrete and compressive strength. A total of four batches of concrete are produced, in which containing 0%, 10%, 20% and 30% laterite agggregate in concrete. In this experiment, properties of laterite aggregate are tested in term of strength,shape and surface texture. As for fresh concrete, slump, compacting factor and vebe consistometer are tested for the respective batches of the concrete mix. For hardened concrete only compressive strength is tested. All the tests have been carried out and the results had been recorded and analyzed in appropriate table and graph. The experimental results show that the strength of laterite aggregate concrete is lower than the granite aggregate concrete.